2019
DOI: 10.1007/jhep07(2019)178
|View full text |Cite|
|
Sign up to set email alerts
|

Classifying 5d SCFTs via 6d SCFTs: rank one

Abstract: Following a recent proposal, we delineate a general procedure to classify 5d SCFTs via compactifications of 6d SCFTs on a circle (possibly with a twist by a discrete global symmetry). The path from 6d SCFTs to 5d SCFTs can be divided into two steps. The first step involves computing the Coulomb branch data of the 5d KK theory obtained by compactifying a 6d SCFT on a circle of finite radius. The second step involves computing the limit of the KK theory when the inverse radius along with some other mass paramete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
206
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(216 citation statements)
references
References 31 publications
2
206
0
1
Order By: Relevance
“…In this smooth space, one can in principle read off all necessary physical data such as the effective gauge descriptions and their mass deformations. There are ongoing efforts, for example in [73,74], towards classifying the smooth geometries associated with marginal theories arising from 6d SCFTs classified by F-theory.…”
Section: D Marginal Theoriesmentioning
confidence: 99%
“…In this smooth space, one can in principle read off all necessary physical data such as the effective gauge descriptions and their mass deformations. There are ongoing efforts, for example in [73,74], towards classifying the smooth geometries associated with marginal theories arising from 6d SCFTs classified by F-theory.…”
Section: D Marginal Theoriesmentioning
confidence: 99%
“…In that paper it was shown that if a 5d single gauge node quiver was to lead to an interacting SCFT in the UV then the matter content (and where relevant the Chern-Simons level) must satisfy the 12 We remind the reader that by a "pure-gauge" quiver we mean a quiver consisting only of gauge nodesthere remain bifundamental matter fields between these gauge nodes. 13 For low ranks these constraints will, in fact, generally be enough to completely fix Qs.…”
Section: Constraints On Quiver Gauge Theoriesmentioning
confidence: 99%
“…Below each embedding of the BG-CFD into the marginal CFD we list the classical flavor symmetry. and only allows gauge descriptions with gauge and flavor ranks given by (r G , r F ) =(5,13) .…”
mentioning
confidence: 99%
“…For Case 3, the parameter region should be further divided into two parts as 16) in the Weyl chamber (A.12). Finally, we discuss the conditions for physical Coulomb moduli in the different Weyl chambers of the E 8 .…”
Section: Sp(2) + 1as + 1fmentioning
confidence: 99%
“…As many of such 5d N = 1 theories can be engineered via Type IIB 5-brane webs [12,13] or M-theory on Calabi-Yau (CY) threefold [14,15], brane configurations also provide a direct description of the prepotential. For instance, one can study CY geometry of 5d gauge theories to obtain their triple intersections which yield the prepotential of the 5d theories or one can also scan possible gauge theory descriptions from the geometry which lead to a classification of the UV-dual theories [6,9,11,[16][17][18][19]. Though Type IIB 5branes can be understood as dual description of the geometry, not all CY geometries can be realized as a 5-brane web.…”
Section: Introductionmentioning
confidence: 99%